1993
DOI: 10.2355/isijinternational.33.1182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Composition on Apparent Viscosity of Semisolid Alloys.

Abstract: ,.Chuo-ku.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…P increased with increasing carbon content while f scr decreased with increasing carbon content. Previous study 7) showed that a higher solute concentration in an alloy led to the formation of rosette-type crystals, resulting in particles with relatively large surface areas and irregular, non-spherical shapes. Therefore, the geometrical shape parameter of the crystals "P" became larger with increasing solute concentrations in melts and the volume fraction of liquid trapped between the primary crystals increased, and thus the critical solid fraction, f scr became smaller.…”
Section: Apparent Viscosity Model For Fe-c Melts Duringmentioning
confidence: 97%
See 4 more Smart Citations
“…P increased with increasing carbon content while f scr decreased with increasing carbon content. Previous study 7) showed that a higher solute concentration in an alloy led to the formation of rosette-type crystals, resulting in particles with relatively large surface areas and irregular, non-spherical shapes. Therefore, the geometrical shape parameter of the crystals "P" became larger with increasing solute concentrations in melts and the volume fraction of liquid trapped between the primary crystals increased, and thus the critical solid fraction, f scr became smaller.…”
Section: Apparent Viscosity Model For Fe-c Melts Duringmentioning
confidence: 97%
“…It was found that the viscosity depended on the solid fraction, the cooling rate, and the shear rate, and the viscosity was influenced more by the cooling rate than the shear rate. Hiral et al 7) quantified the effect of chemical compositions on viscosity of several semi-solid alloys such as Al-Cu, Al-Si, Cu-Sn, and Fe-C (0.8 and 2.5%C). In this research, a uniform predicting model on apparent viscosity was obtained, where the density of alloys (termed as ρ m in that research) was utilized as an important parameter to characterize the effect of chemical compositions on apparent viscosity of semi-solid alloys.…”
Section: Measurement and Characterization Of The Apparent Viscosity Omentioning
confidence: 99%
See 3 more Smart Citations